2023
DOI: 10.1038/s41377-023-01143-0
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-thin light-weight laser-induced-graphene (LIG) diffractive optics

Abstract: The realization of hybrid optics could be one of the best ways to fulfill the technological requirements of compact, light-weight, and multi-functional optical systems for modern industries. Planar diffractive lens (PDL) such as diffractive lenses, photonsieves, and metasurfaces can be patterned on ultra-thin flexible and stretchable substrates and be conformally attached on top of arbitrarily shaped surfaces. In this review, we introduce recent research works addressed to the design and manufacturing of ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 144 publications
0
8
0
Order By: Relevance
“…Laser technology is widely used in the field of flexible material manufacturing and can be used for the fabrication of bio-sensors, soft electronic devices and e-skin. 98–103 In a recent study, three-dimensional integrated electronic devices made of elastomers were reported, where laser ablation and controlled soldering were used to create vertical interconnect accesses (VIA). The pattern designs of the electrodes, heaters, and VIA connectors were all fabricated using the laser ablation technique (Fig.…”
Section: Low-cost Methods For the Fabrication Of Soft Robotic E-skinmentioning
confidence: 99%
“…Laser technology is widely used in the field of flexible material manufacturing and can be used for the fabrication of bio-sensors, soft electronic devices and e-skin. 98–103 In a recent study, three-dimensional integrated electronic devices made of elastomers were reported, where laser ablation and controlled soldering were used to create vertical interconnect accesses (VIA). The pattern designs of the electrodes, heaters, and VIA connectors were all fabricated using the laser ablation technique (Fig.…”
Section: Low-cost Methods For the Fabrication Of Soft Robotic E-skinmentioning
confidence: 99%
“…In comparison to other methods, the LDW method opens up new ideas for the synthesis of photoactive materials owing to its low cost, chemical-free process, and absence of a mask for custom patterning. 26 The LDW method is simple and convenient and can simultaneously synthesize LIG and metal oxides in situ on electrodes via the action of laser beam without a template. 27…”
Section: Introductionmentioning
confidence: 99%
“…Graphene with excellent electrical, mechanical, and thermal performance has drawn tremendous attention in nanoscale electronic devices. Among its numerous analogues, graphene nanoribbons (GNRs) are highly expected in nanoelectronics and sensors. Especially, high sensitivity to external stimuli has been demonstrated in low dimensional ultralong GNRs with large aspect ratios, , which show great potential in developing high performance devices. However, achieving a nanoribbon structure with designed geometry can be quite challenging due to the difficulty in energy or mass control at small scale.…”
Section: Introductionmentioning
confidence: 99%